150k views
1 vote
6x=3(x - 4) - x plzz

User Jessyca
by
4.9k points

2 Answers

4 votes

Answer:

-4

Explanation:

6x = 3(x - 4)

6x = 3x - 12

3x = -12

x = -4

Best of Luck!

User Istiaque Ahmed
by
5.1k points
4 votes

Answer:

x = - 3

Explanation:


6x=3(x - 4) - x

Multiply the terms in the bracket

That's


6x = 3x - 12 - x \\ 6x = 2x - 12

Subtract 2x from both sides of the equation


6x - 2x = 2x - 2x - 12 \\ 4x = - 12

Divide both sides by 4


(4x)/(4) = - (12)/(4)

We have the final answer as

x = - 3

Hope this helps you

User Sgibb
by
5.1k points